232k views
0 votes
(x-2)(x² – 8x+7)=0
Please help me with the steps

2 Answers

3 votes

Answer:

x1 = 1, x2 = 2, x3 = 7

Explanation:

(x-2) x (x² -8x + 7) = 0

When the product of factors equals , at least one factor is 0.

x-2=0

x² -8 + 7=0

Solve the equation for X.

x-2=0

x=2

x² -8+7=0

x=7

x=1

The final solutions are

x1 = 1, x2= 2, x3=7

User Ricovitch
by
5.3k points
5 votes

Answer:

x = 2; x = 1 ; x =7

Explanation:

x² – 8x+7 = x² - x - 7x + 7

= x ( x - 1 ) - 7(x -1)

= (x-1) (x-7)

(x-2)(x² – 8x+7)=0

(x-2)(x - 1) (x - 7)=0

x- 2 = 0 ; x - 1 = 0 ; x- 7 = 0

x = 2; x = 1 ; x =7

User Pinkal Vansia
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.